Asymptotic stability of Markov operators corresponding to the dynamical systems with multiplicative perturbations - Oczkowicz, Katarzyna (Annales Mathematicae Silesianae, 1993)
We consider discret time dynamical systems with multiplicative perturbations. We give a sufficient condition for the asymptotic stability of Markov operators on measures generated by dynamical systems with multiplicative perturbations.